Perfil profesional del dirigente deportivo regional: Valle del Cauca y Risaralda (2017)
The country’s sport authorities have had two major problems: for government officials at the territorial sport entities, the people who are chosen have influence in politics; and regarding the private sector, associate sector, they are chosen for being ex-athletes or an athlete’s relative, without taking into account their knowledge on the sector’s functions and abilities. The second problem refers to their training. The current sports managers do not have an academic background that grants the necessary competences to put into practice an appropriate management (or quality management), the academic background in administration and sports management, the knowledge of the sector and the use of a second language. They usually comply with the 40 hours that are requested to hold a sports management position, according to the 00547 resolution of 2010 by Coldeportes.If the aim is to achieve significant results and the sector’s development, a sports manager has to be a well prepared manager to assume effectively the management and administration of the sport products and services. The current study about the career profile of the regional sports manager – Valle del Cauca and Risaralda, goes hand in hand with the sector’s public politics sports ten-year plan, the recreation, the physical activity and the physical education in Colombia for human development, cohabitation and peace 2009-2019, which first lineament is addressed to the strengthening of the sector’s organizations and in order to achieve that competent sports managers are required. It is a descriptive study, developed through a survey that was administered to the total population, sports leagues presidents of the two states (Valle del Cauca and Risaralda), which main characteristic is to know their academic background in sports management and administration and their experience in the sector’s managing positions.